Thrombospondin-1 Partly Mediates the Cartilage Protective Effect of Adipose-Derived Mesenchymal Stem Cells in Osteoarthritis - Maumus, Marie; Manferdini, Cristina; Toupet, Karine; Chuchana, Paul; Casteilla, Louis; Gachet, Mélanie; Jorgensen, Christian; Lisignoli, Gina; Noël, Danièle (Frontiers in Immunology, 2017)
Objective: Assuming that mesenchymal stem cells respond to the osteoarthritic (OA) joint environment to exert a chondroprotective effect, we aimed at investigating the molecular response set up by MSCs after priming by OA chondrocytes in cocultures. Methods: We used primary human OA chondrocytes and adipose stem cells (ASCs) in mono- and cocultures and performed a high throughput secretome analysis. Among secreted proteins differentially induced in cocultures, we identified thrombospondin-1 (THBS1) as a potential candidate that could be involved in the chondroprotective effect of ASCs. Results: Secretome analysis revealed significant induction of THBS1 in ASCs/chondrocytes cocultures at mRNA and protein levels. We showed that THBS1 was up-regulated at late stages of MSC differentiation towards chondrocytes and that recombinant THBS1 exerted a prochondrogenic effect on MSC indicating a role of THBS1 during chondrogenesis. However compared to control ASCs, siTHBS1-transfected ASCs did not decrease the expression of hypertrophic and inflammatory markers in OA chondrocytes, suggesting that THBS1 was not involved in the reversion of OA phenotype. Nevertheless, down-regulation of THBS1 in ASCs reduced their immunosuppressive activity, which was consistent with the anti-inflammatory role of recombinant THBS1 on T lymphocytes. THBS1 function was then evaluated in the collagenase-induced OA model by comparing siTHBS1-transfected and control ASCs. The protective effect of ASCs evaluated by histological and histomorphological analysis of cartilage and bone was not seen with siTHBS1-transfected ASCs. Conclusion: Our data suggest that THBS1 did not exert a direct protective effect on chondrocytes but might reduce inflammation, subsequently explaining the therapeutic effect of ASCs in OA.